3, 3-Dimethoxypropylsulfonyl Group: A new versatile protecting and activating group for amine synthesis. Issue 24 (14th June 2018) - Sakamoto, Izumi; Iwaoka, Kazuya; Kawada, Yuta; Naito, Takanori; Makida, Kazuyoshi; Takeuchi, Yuki; Nishii, Takeshi; Horikawa, Mitsuyo; Kaku, Hiroto; Tsunoda, Tetsuto
Abstract: 3, 3-Dimethoxypropylsulfonyl (Dimps) chloride was prepared and used as a new versatile sulfonating agent for ammonia, primary and secondary amines to afford corresponding Dimps-amides in excellent yields. The resulting N -nonsubstituted and N -monosubstituted Dimps-amides, activated amines, were alkylated satisfactorily under new Mitsunobu conditions. The Dimps group was removed by treatment in aqueous solution under acidic followed by basic conditions. Furthermore, epilachnene, the defensive droplets from the Mexican bean beetle, Epilachna varivestis, was synthesized utilizing this Dimps methodology in short steps. Graphical abstract: